Telaah Argumen Yang Mendukung Dan Menentang Peraturan Pemerintah No 80 Tahun 2019 Tentang Perdagangan Melalui Sistem Elektronik - Ni Made Trisna Dewi; I Wayan Partama Putra (Fakultas Hukum, Universitas Warmadewa, 2024)
Business activities in e-commerce are currently rising in Indonesia along with the appearances of its regulations, like Government regulation 80/2019 which is creating pros and cons. This writing’s purpose is to analyze impacts from that particular regulation. The regulation creates better nuance in e-commerce for consumers, but doesn’t engage with small and temporary businesses. The regulation helps in regard to tax counting in e-commerce, but creates injustice between small offline and online UMKM in taxation. The regulation made the use of domain id as mandatory, while it shows national identity it’s also advancing portal’s access time due to the server that locates in Indonesia, however it’s rejected by Idea due to the consideration of domain as identity. Businessmen in e-commerce could transmigrate to platforms that are harder to reach by government's regulation. The regulation brings many good changes while also vulnerable to create harm.